Editorial Comments (Orfeu, 2018)
We are pleased to announce the release of the special issue on the Psychology of Music of the ORFEU Journal (vol.3, no.1), edited by the guest editors Dr. Luciana Hamond (PPGMUS / UDESC) and Professor Graham Welch (UCL Institute of Education, UK).